2014
DOI: 10.5897/ajest2013.1622
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of intestinal protozoan parasites from children facing diarrheal disease and associated risk factors in Yamoussoukro, Cte dIvoire

Abstract: Diarrheal diseases are very common in children under 5 years and may lead to a delay of physical and mental development. Despite this knowledge, data on diarrheal diseases and socioeconomic determinants are still scarce in Côte d'Ivoire. This study is then conducted with the objective to fill part of this gap and specifically assess link between infant diarrhea occurrence and some major socioenvironmental factors. Stool samples were collected from children less than five suffering from diarrhea at Yamoussoukro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…Statistical analysis showed that there were significant differences in the incidence rates between age at the probability level p≤ 0.01. This result is consistent with the result (32) in Kirkuk, in his study on E. Histolytica and G. lamblia which recorded that the incidence of E.histolytica was significantly higher in less than 10 years (60%),and the result of (33) in Erbil governorate reported (38%) in the age group (1-12 years), and the result of (34) in Côte d'Ivoire. The reason for the high incidence of infection in the age groups (10-1) years is due to several factors, including: the fact that children are less resistant to infection compared to adults due to the incompleteness and maturity of their system, and that children are usually in a state of contact with the environment as well as mixing with each other, especially in schools and kindergartens Children As for the low incidence of infection in the age groups (60-51) years, it is due to the increase in health awareness and the development of their immune system.…”
Section: Resultssupporting
confidence: 92%
“…Statistical analysis showed that there were significant differences in the incidence rates between age at the probability level p≤ 0.01. This result is consistent with the result (32) in Kirkuk, in his study on E. Histolytica and G. lamblia which recorded that the incidence of E.histolytica was significantly higher in less than 10 years (60%),and the result of (33) in Erbil governorate reported (38%) in the age group (1-12 years), and the result of (34) in Côte d'Ivoire. The reason for the high incidence of infection in the age groups (10-1) years is due to several factors, including: the fact that children are less resistant to infection compared to adults due to the incompleteness and maturity of their system, and that children are usually in a state of contact with the environment as well as mixing with each other, especially in schools and kindergartens Children As for the low incidence of infection in the age groups (60-51) years, it is due to the increase in health awareness and the development of their immune system.…”
Section: Resultssupporting
confidence: 92%
“…The study showed that the E. histolytica was considerably more prevalent in the age group <1-3 years (62.9%) and lower in the age group 10-12 years(3.8%), this variation was high significant (P = <0.0001),as summaries in (Table 5). The results of the present study was agree with Ahmed's study 2016(4) which found higher rate of infection in age group (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and (25-36)months after examined 185 diarrheal children. Mathurin and his team (20)which reported that the age group 0-24 months and 5-36 months showed high rate of E. histolytica infection while, fewer infections were detected in the older children.…”
Section: Distribution Of the Patients According To The Age Groupssupporting
confidence: 92%
“…The results of the present study was agree with Ahmed's study 2016(4) which found higher rate of infection in age group (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months and (25-36)months after examined 185 diarrheal children. Mathurin and his team (20)which reported that the age group 0-24 months and 5-36 months showed high rate of E. histolytica infection while, fewer infections were detected in the older children. Otherwise, the current study disagrees with Hamad and Ramzy(24) they found that the children less than 1 year old had a lower rate of E. histolytica infection.…”
Section: Distribution Of the Patients According To The Age Groupssupporting
confidence: 92%
“…This is parallel with previous studies. 47,48 This might be contributed by the presence of resistant cysts of the parasites for routine chemical treatments like wuha agar and chlorine and the well water in the study area is unprotected; hence, it contains high number of pathogens. Similarly, those who had not washed their hands before the meal were 3.3 times at high risk of acquiring protozoan infections than those who were washing their hands before a meal.…”
Section: Discussionmentioning
confidence: 99%